Comparison of the worst-case scenarios between training and competition weeks for each playing position in an elite football season - Díez, A.; Bataller-Cervero, A. V.; Mainer-Pardos, E.; Roso-Moliner, A.; Arjol-Serrano, J. L.; Lozano, D. (Biology of Sport, 2025)
The aim of this study was to examine the worst-case scenarios (WCS) produced during the week in training sessions and compare them with the physical demands of the matches. A total of 194 training sessions and 42 matches were analysed during the 2020/2021 season in the Second Spanish Football League. Data were collected using Global Positioning System devices. Players were grouped according to their playing positions into central defenders, wide players, midfielders (MID), and forwards. The variables analysed were distance, HSR distance, sprint distance, high acceleration, high deceleration, and high metabolic load distance. The most demanding passages were analysed in 1-minute periods using the rolling average method. The most significant differences were found in the HSR distance (p < 0.001; np2 = 0.854), sprint distance (p < 0.001; np2 = 0.882) and high metabolic load distance (p < 0.001; np2 = 0.899) variables on the day furthest from the match day. No significant differences were found in the data analysed for MID in any training session of the week compared with the match, nor in the variables of high acceleration and high deceleration. Knowledge about the worst-case scenario during a competitive microcycle can help understand the physical level and individual requirements that our players need to perform at a high level on the match day, as well as preventing possible injuries or fatigue.